Bernstein-type inequalities for $\mathcal{L}$-splines - Babenko, V. F.; Ligun, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
New Berhstein-type inequalities are obtain for 2π-periodic $\mathcal{L}$ -splines associated with a differential operator $\mathcal{L}_τ (D)$ of degree $r$ with fixed real coefficients.